Cymbopogon nardus Leaf Ash as an Alternative Material for Enhancing Concrete Strength - Bunyamin, Bunyamin; Munirul, Hady; Reza Pahlevi, Munirwan; Putra Jaya, Ramadhansyah (Hindawi, 2024)
Numerous waste materials containing calcium and silica have been adopted as partial cement substitutes. This practice is intended to reduce the environmental impact of cement production, specifically in terms of carbon dioxide (CO2) emissions. However, plantation waste, specifically waste from Cymbopogon nardus leaf, has not been completely exploited. The presence of silica in C. nardus leaf ash (CNLA) presents an opportunity to partially replace cement in concrete. The purpose of this study is to determine the effect of substituting CNLA at 0%, 5%, 10%, and 15% as a partial replacement for cement on the compressive and tensile strengths of concrete after 28 days of curing. For testing purposes, 15 cm × 30 cm cylindrical concrete specimens were formed. The investigation was conducted following ACI 211.1-91 (American Concrete Institute) and ASTM (American Society for Testing and Materials) standards. The required compressive strength for the concrete was 17.00 MPa. The results of the study indicate that the addition of CNLA to cement at concentrations of 0%, 5%, 10%, and 15% resulted in compressive strengths of 21.56, 21.12, 22.58, and 17.88 MPa, respectively. The results of the split tensile strength test were 2.43, 2.72, 2.87, and 3.18 MPa, respectively. According to the findings of this study, increasing the amount of CNLA in cement by 10% can increase the compressive and tensile strengths of concrete. In addition, as the percentage of CNLA exceeds 10%, the workability of the concrete decreases, posing challenges in attaining the targeted strength of the concrete.